Copulatory plugs inhibit the reproductive success of rival males - Mangels, Rachel (J Evol Biol, 2016)
Ejaculated proteins play important roles in reproductive fitness. In many species, seminal fluid coagulates and forms what has been referred to as a copulatory plug in the female's reproductive tract. In mice, previous work demonstrated that knockout males missing a key seminal fluid protein were unable to form a plug and less successful at siring litters in non-competitive matings (one female, one male), probably the result of reduced sperm transport or insufficient stimulation of the female. Here we extend these previous studies to competitive matings (one female, two males), and make two key insights. First, when first males were unable to form a plug, they lost almost all paternity to second males to mate. Thus, the copulatory plugs of second males could not rescue the reduced fertility of first males. Second, we showed that the copulatory plug of first males effectively blocks fertilization by second males, even if first males are vasectomized. Taken together, our experiments demonstrate that first males lose almost all paternity if they never form a plug. We discuss our results in the context of natural populations, where in spite of the strong effects seen here, pregnant female mice regularly carry litters fertilized by more than one male.